Universal Health Coverage in the Philippines : Progress on Financial Protection Goals - Bredenkamp, Caryn; Buisman, Leander R. (World Bank, Washington, DC, 2015)
Providing protection against the financial risk of high out-of-pocket health spending is one of the main goals of the Philippines’ health strategy. Yet, as this paper shows using eight household surveys, health spending increased by 150 percent (real) from 2000 to 2012, with the sharpest increases occurring in recent years. The main driver of health spending is medicines, accounting for almost two-thirds of total health spending, and as much as three-quarters among the poor. The incidence of catastrophic payments has trebled since 2000, from 2.5 to 7.7 percent. The percentage of people impoverished by health spending has also increased and, in 2012, out-of-pocket spending on health added 1.5 percentage points to the poverty rate. In light of these findings, recent policies to enhance financial risk protection—such as the expansion of government-subsidized health insurance for the poor, a deepening of the benefit package, and provider payment reform aimed at cost-containment—are to be applauded. Between 2008 and 2013, self-reported health insurance coverage increased across all quintiles and its distribution became more pro-poor. To speed progress toward financial protection goals, possible quick wins could include issuing health insurance cards for the poor to increase awareness of coverage and introducing a fixed copayment for non-poor members. Over the medium term, complementary investments in supply-side readiness are essential. Finally, an in-depth analysis of the pharmaceutical sector would help to shed light on why medicines continue to place such a large financial burden on households.